High columns, high risk: point-load-driven convergence in deep cave mining - van As, A.; Van Hout, G. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The progressive increase in cave column heights in modern cave mining operations has fundamentally changed the dominant damage mechanisms acting on the extraction level, shifting from undercut-induced abutment stress damage to overburden weighting and highly localised point loading as the dominant failure modes. Consequently, the primary geotechnical challenge has moved from cave propagation, ore recovery, and draw performance to preserving the extraction level under extreme loading conditions. In deep, high-column cave mines, severe convergence is increasingly driven by column loading and the mobilisation of large, partially dislodged rock masses bounded by faults and major structures, which impose concentrated loads on the extraction level, particularly in the vicinity of faults or areas of weaker rock mass. Under these conditions, crushing with the consequent loss of extraction level functionality and productivity has emerged as the dominant life-of-mine risk. This paper argues that conventional draw control philosophies, historically centred on maximising recovery and minimising dilution, are no longer sufficient, nor primary, in deep, high-column cave environments. The established principles of cave draw control remain valid and are not superseded; however, they do require modification. Draw control must also be reframed as a stress/damage management tool, with the objective of actively managing point loading and convergence through deliberate load shedding. Two structured load shedding strategies are examined: sequenced strip drawing (SSD), a shift-to-shift sequencing discipline for ongoing stress redistribution across the extraction level footprint, and targeted load redistribution draw (TLRD), a spatially focused strategy for reducing significant convergence or point load events by increasing porosity and draw cone interaction in the affected zone. Both recognise that productivity-focused (often automated) draw strategies become secondary considerations once extraction level preservation is at risk. A critical and related concern is the growing incompatibility between modern cave layouts and effective load shedding. Increasing drawpoint spacings and correspondingly larger pillar dimensions are reducing the likelihood of drawzone interaction, limiting the ability to shed load efficiently, and exacerbating stress concentrations within oversized pillars. This design parameter must be critically re-examined. The paper concludes that the long-term viability of deep, high-column cave mining will require a paradigm shift in cave mine design philosophy, including reduced block heights and multiple lifts, smaller pillars, and layouts that deliberately promote drawzone interaction, together with new technologies capable of facilitating rapid, reliable load shedding. Current numerical modelling approaches are also identified as insufficiently reliable in capturing the onset and progression of extraction level damage under these conditions, owing to structural uncertainty and the transient, localised nature of point loading.